"Kissing Molars" - A Case Report - Jigna Shah; Shweta Goel (Wolters Kluwer Medknow Publications, 2007)
Impaction of permanent molars is as such a common condition, but phenomenon of "kissing molars" where occlusal surfaces of impacted molars facing each other is an uncommon radiological finding. A case is presented of "kissing molars" where occlusal surfaces of permanent second and third molars are in close proximity in a patient with ankylosis of TMJ. As such various causes can be linked with this condition but in this case the prime cause for this condition can be considered narrow arch length as patient was having TMJ ankylosis.